3D printing of a gradient-patterned tubular scaffold for central nervous system regenerative applications - Hamid, Omar Abdulhakeem (2018)
During the central nervous system (CNS) morphogenesis, chemical gradients of morphogens such as retinoic acid (RA) or sonic hedgehog play a central role in regulating CNS patterning and differentiation of neural subtypes. Recapitulation of these gradients in a 3D hydrogel matrix may provide a model for CNS tissue formation in vitro. 3D Printing technology offers an opportunity to reproduce the complex architecture of cell microenvironment. We have developed a 3D-printable alginate hydrogel bioink suitable for extrusion-based bioprinting. The bioink was characterised by shear thinning, high printing resolution and minimal adverse effects on cell viability. The bioink was successfully used to print mouse embryonic stem cells (mESCs)-laden constructs and supported their differentiation into neural-like cells. Extrusion-based bioprinting was used to 3D-print hybrid polycaprolactone (PCL)-alginate tubular scaffolds functionalised with a fluorescein isothiocyanate-conjugated bovine serum albumin (FITC-BSA) concentration gradient pattern. Quantification of the FITC-BSA concentrations in the scaffold showed a linear reduction in concentration as a function of scaffold’s distance (length). Tubular scaffolds printed with fibroblast-laden alginate supported cell viability and proliferation up to 6 days after printing. Next, the developed model was used to replicate the in vivo RA-induced directed differentiation of mESCs into spinal cord neurons. RA-concentration-dependent acquisition of neural identity was investigated using immunocytochemistry and flow cytometry analysis. RA promoted the formation of neurons with hindbrain and spinal cord identity and supressed the forebrain identity in a concentration-dependent manner. Among the investigated hydrogels, gelatine methacrylate (GelMA) supported neural differentiation and neurite outgrowth of the mESCs-derived embryoid bodies (EBs). Subsequently EBs-laden GelMA (5%) was successfully used as a bioink to print the hybrid PCL-hydrogel scaffolds. 3D Printing of EBs and RA-loaded GelMA in PCL scaffold induced differentiation of EBs into neurons with spinal cord positional identity. In conclusion, the model can be used for effective morphogens gradients delivery to replicate some of the complex processes of CNS development in vitro.